1995
DOI: 10.1021/ic00112a027
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Growth: Some Representative Reactions. Crystal Structures of [Pt(H)(AgNO3)(AuPPh3)8](NO3) and [Pt(H)(AgNO3)2(AuPPh3)8](NO3)

Abstract: The reaction of [Pt(AuPPh3)8](N0 3 )2 with AgNC>3 under H2-atmosphere yields two new hydride-containing P t-A u -A g cluster compounds: [Pt(H)(AgN0 3 )(AuPPh3)8](N0 3 ) (1) and [Pt(H)(AgN03)2(AuPPh3)8](N03) (2). These reactions show intimate details on cluster growth: the nine-metal-atom particle [Pt(AuPPh3)8](N0 3)2 grows via oxidative addition of H2, deprotonation and electrophilic addition o f Ag+ to a 10-and then to an 11-metal-atom particle, 2. Cluster compounds 1 and 2 were characterized by elemental ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…However, it is still a challenge to obtain the doped clusters with the desired composition in high yield due to the difference in the relative reduction rates of the precursor metal ions. To circumvent the difficulties, other methods such as galvanic and antigalvanic methods have been developed. ,,,, Tri- and tetrametallic clusters have been synthesized by antigalvanic processes between preformed bimetallic clusters and heterometal complexes and reduction of heterometal precursors in the presence of preformed bimetallic clusters. …”
Section: Introductionmentioning
confidence: 99%
“…However, it is still a challenge to obtain the doped clusters with the desired composition in high yield due to the difference in the relative reduction rates of the precursor metal ions. To circumvent the difficulties, other methods such as galvanic and antigalvanic methods have been developed. ,,,, Tri- and tetrametallic clusters have been synthesized by antigalvanic processes between preformed bimetallic clusters and heterometal complexes and reduction of heterometal precursors in the presence of preformed bimetallic clusters. …”
Section: Introductionmentioning
confidence: 99%
“…Steggerda et al reported a similar growth reaction of [PtAu 8 (PPh 3 ) 8 ] 2+ using H 2 under basic conditions. , First, [Pt­(H 2 )­Au 8 (PPh 3 ) 8 ] 2+ is produced by dissociative adsorption of H 2 on [PtAu 8 (PPh 3 ) 8 ] 2+ and a proton is subsequently abstracted from [Pt­(H 2 )­Au 8 (PPh 3 ) 8 ] 2+ by the base (such as pyridine) to form [Pt­(H)­Au 8 (PPh 3 ) 8 ] + . Finally, a coinage metal cation can be introduced to form [Pt­(H)­(X) n Au 8 (PPh 3 ) 8 ] + (X = Au + , Ag + , Cu + ; n = 1, 2).…”
mentioning
confidence: 97%
“…For most of them the metallic frameworks can be derived from a Pt-centered Au 12 icosahedron by removing seven [41], six [555,556], four [556,558], three [548,[559][560][561], or two [556] vertices. Clusters with similar cores in which up to three gold atoms are replaced by atoms of another metal have also been reported, for example, Pt-Au 5 Pt 2 [550], Pt-Au 6 Hg [42], Pt-Au 5 Hg 2 [41], Pt-Au 8 Ag [556,562,563], Pt-Au 8 Ag 2 [563], Pt-Au 8 Cu [556,564] and Pt-Au 8 Cu 2 [564]. In another few compounds additional metal atoms are connected to an M 3 face of trimetallic frameworks derived from Pt-centered icosahedra, for example, Cu(Pt-Au 6 Cu 3 ) [565] and Ag 2 (Pt-Au 6 Recently, the first nanosized Au/Pt cluster, [(Ph 3 P) 2 Au 2 ] 2 Pt 13 (CO) 10 (PPh 3 ) 4 411, was reported; it contains a Pt-centered Pt 12 icosahedral cage capped by two (Ph 3 P)AuAu(PPh 3 ) units [567].…”
Section: Gold-group 9 Metal Compoundsmentioning
confidence: 99%